An innovation approach of multiple discharging channels in EDM precision machining by a novel adaptive gap voltage control system. Issue 5 (March 2019) - Mu, Xin; Zhou, Ming
Abstract: For decades, two issues, hard-to-improved machined surface roughness and low machining rate, have hindered the further developments of electrical discharge machining (EDM) Tool in precision manufacturing. In precision EDM, keeping a large gap distance is the only way for conventional EDM to obtain the integrity of a machined surface. However, the fact is large gap distances really prevented further improving machined surface quality and meanwhile lowered machining rate as well. Conversely, this paper tried to take small gap distances so that a discharging mechanism of generating multi-discharging channels from one pulse could be realized. The consequences were that both much greater improved machined surfaces and fast machining rates were obtained in addition to the more integrated machined surface than the conventional EDM did. To this end, a novel EDM adaptive control system was studied in this paper where arcing ratio was a control indicator and gap voltage was a control parameter. By presetting an arcing ratio expected value, arcing ratio can follow the value all the time by adapting gap voltage so that arcing pulses could not take place in the gap and thus the integrity of the machined surface can be obtained. By properly setting arcing ratio expected value, gap voltages could be adapted low enough with respect to arcing ratios so that multi-discharging channels from one pulse could be formed. Comparison experiments not only proved the effectiveness of the EDM adaptive control system but also demonstrated the feasibility of forming multi-discharging channels from one pulse in precision machining. Compared with conventional EDM, in addition to the more integrated machined surface had been obtained the surface roughness had been lowered almost 4 times and the machining rate improved 2.7 times. The significance of the study is that forming multi-discharging channels from one pulse displayed an innovative approach in precision EDM.